2021
DOI: 10.3390/biomedicines9111520
|View full text |Cite
|
Sign up to set email alerts
|

Topical Administration of Heat-Killed Enterococcus faecalis Strain KH2 Promotes Re-Epithelialization and Granulation Tissue Formation during Skin Wound-Healing

Abstract: Lactic acid bacteria (LAB) are known to have beneficial effects on immune responses when they are orally administered as bacterial products. Although the beneficial effects of LAB have been reported for the genera Lactobacillus and Lactococcus, little has been uncovered on the effects of the genus Enterococcus on skin wound-healing. In this study, we aimed to clarify the effect of heat-killed Enterococcus faecalis KH2 (heat-killed KH2) strain on the wound-healing process and to evaluate the therapeutic potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…We found that samples from skin with lower grades of wrinkles were associated with some commensal taxa such as the genera Staphylococcus, Kocuria , Peptostreptococcus , and Lysobacter, ( Figure 3A ). ( Tanno et al, 2021 ; Lebeer et al, 2022 ; Zanchetta et al, 2022 ) Our results also identified environment-related bacteria including Brevibacterium and Kaistella that are often associated with skin alterations and inflammatory conditions such as psoriasis and senile xerosis ( Huang et al, 2021 ; Li et al, 2021 ). These taxa were enriched in the samples from subjects with higher grades of wrinkles ( Figure 3A ).…”
Section: Resultssupporting
confidence: 52%
“…We found that samples from skin with lower grades of wrinkles were associated with some commensal taxa such as the genera Staphylococcus, Kocuria , Peptostreptococcus , and Lysobacter, ( Figure 3A ). ( Tanno et al, 2021 ; Lebeer et al, 2022 ; Zanchetta et al, 2022 ) Our results also identified environment-related bacteria including Brevibacterium and Kaistella that are often associated with skin alterations and inflammatory conditions such as psoriasis and senile xerosis ( Huang et al, 2021 ; Li et al, 2021 ). These taxa were enriched in the samples from subjects with higher grades of wrinkles ( Figure 3A ).…”
Section: Resultssupporting
confidence: 52%
“…Studies found that treating skin wounds with the heat killed KH2 strain of E. faecalis elevated wound healing by increasing the production of inflammatory cytokines, which may be involved in the production of growth factors. Furthermore, increased growth factor production may hasten re-epithelialization, granulation tissue formation, and angiogenesis (Tanno et al 2021 ).…”
Section: Anti-inflammatory Properties Exhibited By Strains Of Lactic ...mentioning
confidence: 99%
“…Although little is known about the effects of heat-killed LAB on the inflammatory responses, including the kinetics of M1 and M2 macrophages, it has been reported that early phase TNF-α synthesis was potentiated after E. faecalis KH2 administration 13 and that neutrophil myeloperoxidase (MPO) activity was ameliorated in the proliferative phase after L. chungangensis CAU 1447 treatment 15 . In the current study, the topical administration of heat-killed L. plantarum KB131 caused accelerated wound repair that was accompanied by the increased accumulation of neutrophils and M1 macrophages in the early phase and also by the increase of M2 macrophages from the early inflammatory phase to the proliferative phase.…”
Section: Discussionmentioning
confidence: 99%
“…There are safety concerns related to the risks of using live microorganisms, however, such as systemic infections and excessive inflammatory responses 11 , 12 . Against this background, recent research has focused on the contribution of heat-killed LAB to wound healing 13 15 . It has been reported that heat-killed Enterococcus faecalis 13 , L. plantarum GMNL 6 and L. paracasei GMNL 653 14 , or Lactococcus chungangensis CAU 1447 15 leads to improved wound healing in skin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation